EANO guidelines for the diagnosis and treatment of meningiomas - Goldbrunner, Roland; Minniti, Giuseppe; Preusser, Matthias; Jenkinson, Michael D.; Sallabanda, Kita; Houdart, Emmanuel; Deimling, Andreas von; Stavrinou, Pantelis; Lefranc, Florence; Lund-Johansen, Morten; Moyal, Elizabeth Cohen-Jonathan; Brandsma, Dieta; et al. (The lancet. Oncology, 2016)
Summary Although meningiomas are the most common intracranial tumours, the level of evidence to provide recommendations for the diagnosis and treatment of meningiomas is low compared with other tumours such as high-grade gliomas. The meningioma task force of the European Association of Neuro-Oncology (EANO) assessed the scientific literature and composed a framework of the best possible evidence-based recommendations for health professionals. The provisional diagnosis of meningioma is mainly made by MRI. Definitive diagnosis, including histological classification, grading, and molecular profiling, requires a surgical procedure to obtain tumour tissue. Therefore, in many elderly patients, observation is the best therapeutic option. If therapy is deemed necessary, the standard treatment is gross total surgical resection including the involved dura. As an alternative, radiosurgery can be done for small tumours, or fractionated radiotherapy in large or previously treated tumours. Treatment concepts combining surgery and radiosurgery or fractionated radiotherapy, which enable treatment of the complete tumour volume with low morbidity, are being developed. Pharmacotherapy for meningiomas has remained largely experimental. However, antiangiogenic drugs, peptide receptor radionuclide therapy, and targeted agents are promising candidates for future pharmacological approaches to treat refractory meningiomas across all WHO grades.
Gesehen am 30.06.2020